Target analysis and retrospective screening of contaminants in ready-to-eat cooked ham samples through UHPLC-Q-Orbitrap HRMS. (15th May 2023) - Izzo, Luana; Castaldo, Luigi; Narváez, Alfonso; Gaspari, Anna; Grosso, Michela; Rodríguez-Carrasco, Yelko; Ritieni, Alberto
Highlights: Surveillance studies of regulated veterinary drug residues in ready-to-eat cooked ham. Method validated in accordance with the Implementing Regulation 2021/808. Occurrence of VDs (n = 14) in 38 analyzed samples including colchicine. Abstract: The use of veterinary drugs (VDs) is widely administered to animals for both therapeutic and prophylactic purposes. However, their improper use may involve their occurrence in the final products intended for human consumption. In this scientific work, a method for the investigation of target ( n = 30) VDs residues and retrospective suspect screening followed by confirmation using analytical standards of others 38 contaminants in ready-to-eat cooked ham by ultra-high performance liquid chromatography coupled with high-resolution mass spectrometry (UHPLC-Q-Orbitrap HRMS) was developed. The extraction was performed based on the QuEChERS approach and validated in accordance with the European Regulation 2021/808. The application of the in-house validated method to ready-to-eat cooked ham showed the occurrence of fourteen VDs residues. Despite the important incidence, the concentration levels found were below the maximum residue limits set for VDs in porcine muscle, except for colchicine. Constant monitoring of animals derived food is strongly recommended to ensure the food safety of consumers.